Attitude of dairy farmers towards animal welfare in Haryana - SARITA, SARITA; SINGH, S P (The Indian Journal of Animal Sciences, 2017)
The welfare of production animals provokes wide social discussion among the public. Despite this farmer's voices and their representations of animal welfare are rarely heard even though farmers are the one who actually deal with animals and able to improve animal welfare. Farmer's perceptions of what constitutes animal welfare and how it may be improved can differ from those of consumers and other stakeholders. The present study was conducted on 120 dairy farmers randomly selected from four villages of Hisar district, Haryana to measure their attitude towards animal welfare during 2013-14. A scale developed by Likert's Summated Ratings method was used for measuring the attitude of dairy farmers. The mean attitude score of all respondents indicates that attitude of dairy farmers is highly positive and favourable. Almost 86 per cent of dairy farmers were having favourable and strongly favourable attitude towards animal welfare. Educational qualification, extension contact and mass media exposure had positive and significant relationship with attitude scores of dairy farmers. Regression analysis revealed that all the nine independent variables jointly explained more than half of the variation in attitude scores. The path analysis revealed that social participation had maximum positive direct effect followed by extension contact and mass media exposure. The study validates the fact that the Indian dairy farmers are sensitive to the issues of animal welfare.